Пародія як феномен літературної критики - Науменко, Наталія Валентинівна (My University, 2017)
У статті показано особливості пародії не лише як художнього твору, а й як різновиду літературно-критичної розвідки. Показано, що пародія, котра, за задумом її автора, має на меті показати й висміяти певні вади твору-оригіналу, насправді при уважному прочитанні установлює критичну парадигму, у якій, по-перше, виявлені вади постають як спосіб «творчої профілактики» майбутньому поетові, а по-друге, дозволяють читачеві увиразнити й позитиви пародійованого тексту. The article elucidates the properties of a parody as not only an art work, but also as a literary-critical study. There is shown that the parody, according to the creative invention of its author, has the purpose to expose and then to deride the certain disadvantages of on original poetic text; however, in closer reading, it seems to maintain a critical paradigm. First of all, this paradigm reveals all of the noticed flaws as the remedy to make ‘the creative prophylactics’ for a future poet; second, it helps a reader to comprehend as well the positive features of a parodied text (particularly, in reading an original), and also to imagine the image of an author (of either the original or the parody) opened to further interpretations.
Keywords: пародія; образ; жанр; система віршування; поезія; літературна критика; індивідуальний стиль; individual style; parody; image; genre; versification system; poetry; literary criticism; кафедра гуманітарних дисциплін